ANALISIS FAKTOR – FAKTOR YANG DAPAT MEMPENGARUHI INDEKS PEMBANGUNAN MANUSIA (STUDI KASUS PADA KABUPATEN DAN KOTA DI PROVINSI JAWA TENGAH TAHUN 2013 – 2022) - Putri Azzahro, Edelia; Khasanah, Uswatun (JIDE : Journal Of International Development Economics, 2025)
This research aims to analyze the influence of regional expenditure, unemployment rate, poverty rate, economic growth, education and health on the human development index in 35 districts and cities in Central Java province during 2013 - 2022. Using panel data regression and the FGLS method (Feasible Generalized Least Square). The data used in this research is secondary data obtained from the Badan Pusat Statistik (BPS). This research found that simultaneously all variables have an influence on the human development index. Meanwhile, partially only five of the six variables have a significant influence. These variables are regional spending, poverty level, economic growth, education and health. Meanwhile, the unemployment rate variable shows insignificant results. This research shows that the quality of human capital is very important in developing a region or country. Because quality human resources are able to overcome various problems such as poverty and inequality and can increase economic growth.